Integrated proximal geophysical sensing reveals dominant litho-geomorphological controls over pedogenesis in Atacama desert Aridisols - Guilherme Xavier Moreira; Davi Feital Gjorup; Isabelle de Angeli Oliveira; José João Lelis Leal de Souza; Gustavo Vieira Veloso; Márcio Rocha Francelino; Tiago Osório Ferreira; Raul Roberto Poppiel; José Alexandre Melo Demattê; Emilson Pereira Leite; Marcos Rafael Nanni; Carlos Ernesto Gonçalves Reynaud Schaefer; et al. (CATENA, 2026)

First report of free-ranging maned wolf (Chrysocyon brachyurus) coinfected with Dioctophyma renale and Pearsonema sp. in Brazil - Alexandre Carvalho Costa; Elisabeth Neves Mureb; Naiara Vidal Stocco; Ágatha Ferreira Xavier de Oliveira; Bruna Emely Pereira Barbosa; Cristiano Chaves Pessoa da Veiga; Andresa Guimarães; Juliana Macedo Raimundo; Huarrisson Azevedo Santos; Daniel de Almeida Balthazar; Cristiane Divan Baldani (Veterinary Research Communications, 2026)
The manned wolf ( Chrysocyon brachyurus ) has a highly diversified diet, that includes fish and amphibians, which may harbor infective forms of parasites, such as Dioctophyma renale and Pearsonema (syn. Capillaria ) spp. Both parasites affect the urinary tract of their hosts, with D. renale being capable of infecting a wide range of mammalian species, whereas Pearsonema spp. exclusively parasitizes wild and domestic canids and felids, releasing their eggs in the urine of the host. This study reports the first coinfection by D. renale and Pearsonema sp. in the urine of a free-ranging maned wolf as well as associated laboratory findings. A male adult maned wolf, injured in a train accident in an urban area, was referred to the Centro de Triagem de Animais Silvestres (CETAS) – Rio de Janeiro, Brazil, where hemogram, biochemistry, ultrasonography, and urinalysis were performed. Ultrasonography examination revealed findings consistent with parasitism by D. renale in the right kidney and right perirenal region. Urinary sediment examination showed D. renale (5/field) and Pearsonema sp. eggs (1/field). Egg morphometry was performed, yielding mean length and width values of 62.2 μm and 41.2 μm for D. renale and 58.0 μm and 26.1 μm for Pearsonema sp., respectively. Through sediment examination and morphometry, it was possible to confirm Pearsonema sp. and D. renale infection, the latter also confirmed by ultrasonography, highlighting the importance of urinalysis in wild animals and demonstrating the need for continuous investigation into Pearsonema spp. which are poorly studied in wild canids.

Nonlinear Modeling of Sugarcane Yield Based on Edaphic Attributes and Soil Classes - Tays Silva Batista; Luiz Alexandre Peternelli; Ivan Carlos Carreiro Almeida; André Mundstock Xavier de Carvalho (Sugar Tech, 2026)
Edaphic attributes strongly influence sugarcane yield, yet production environments are commonly classified based on average productivity, which may not fully capture environmental variability. This study evaluated how physicochemical soil attributes and soil classes influence sugarcane productivity and whether integrating nonlinear modeling and multivariate analyses improves the characterization of production environments. Edaphic data obtained from SoilGrids and mean Tons of Stalks per Hectare (TSH) per genotype, environment, and harvest cycle collected between 2018 and 2021 were used. Generalized additive models (GAMs) were fitted to assess the effects of soil classes and continuous soil attributes on productivity, while principal component analysis (PCA) and hierarchical clustering were used to identify edaphic gradients and group environments according to soil similarity. The GAM explained 67% of the variance in TSH and revealed significant nonlinear effects of bulk density, cation exchange capacity (CEC), silt, nitrogen, and organic carbon across soil depths. Soil class also significantly affected productivity, with LATOSSOLO VERMELHO Distrófico (LVd) associated with the highest TSH values. PCA identified two major edaphic gradients related to texture/fertility and surface fertility, and clustering grouped environments into four distinct edaphic profiles. Comparison with the traditional productivity-based classification showed that environments with similar TSH can exhibit markedly different soil characteristics, indicating that average yield alone is insufficient to describe environmental variability. Integrating nonlinear modeling and multivariate soil characterization provides a more informative framework for environmental stratification, supporting genotype recommendation and agronomic management in sugarcane production systems.

Integrative structural and kinetic analysis of the molecular basis for reduced carbamate inhibition in atypical butyrylcholinesterase - Ana Matošević; Nikola Maraković; Danijela Barić; Alexandre Igert; Xavier Brazzolotto; Zrinka Kovarik; Anita Bosak (Chemico-Biological Interactions, 2026)

First report of Fusarium caatingaense causing cutting rot on Passiflora mucronata in Brazil - Vanessa Sessa Dian; Grenville Antonio Souza dos Santos; Patrick Alves de Oliveira; Jordania Bolzan dos Santos; Laiane Silva Maciel; Fernanda Prieto Bruckner; Deyse Ribeiro Silvino de Jesus; Willian Bucker Moraes; Fábio Ramos Alves; Amanda Cupertino de Queiroz Brito; Alexandre Reis Machado; José Carlos Lopes; et al. (Journal of Plant Pathology, 2026)

Mesoscale processes in the northern Arabian Sea: Linking in situ observations to remote-sensing - Criado Léa; Barboni Alexandre; Carton Xavier (Deep Sea Research Part II: Topical Studies in Oceanography, 2025)

Methodology for the assessment of leaf area in fruit tree orchards using a terrestrial LiDAR-based system - Bernat Lavaquiol-Colell; Jordi Llorens-Calveras; Ricardo Sanz; Xavier Torrent; José M. Plata; Alexandre Escolà (Precision Agriculture, 2025)

Multiomic insights into sucrose accumulation in sugarcane - Alexandre Hild Aono; Ricardo José Gonzaga Pimenta; Jéssica Faversani Diniz; Marishani Marin Carrasco; Guilherme Kenichi Hosaka; Fernando Henrique Correr; Ana Letycia Basso Garcia; Estela Araujo Costa; Alisson Esdras Coutinho; Luciana Rossini Pinto; Marcos Guimarães de Andrade Landell; Mauro Alexandre Xavier; et al. (Plant Molecular Biology, 2025)

Safety and efficacy of an intramuscular bivalent vaccine against influenza and Streptococcus pneumoniae infections in mice - Kimberly Freitas Cardoso; Lara Regina Alves de Souza; Débora Silva Martins; Beatriz Senra Álvares da Silva Santos; Ketyllen Reis Andrade de Carvalho; Sarah Giarola da Silva Messias; Ana Paula de Faria Gonçalves; Rayanne Rosa Do Nascimento Macário; Deyse Julia Ferreira de Jesus; Ana Luiza Pessoa De Mendonça Ângelo; Leonardo de Paula Pereira; Sâmick Layene Moreira Nascimento; et al. (Medical Microbiology and Immunology, 2025)

A novel case of feline Exophiala spinifera disease in Americas: review integrating diagnosis and clinical - Mariana Almeida Ferreira; Gabrielle Silveira Vargas; João Vitor Gregolan Barbosa; Allana de Paula Castilho; Ingrid Gonçalves Costa Leite; Jandra Pacheco dos Santos; Marina Pacheco Miguel; Tiago Alexandre Cocio; Roseli Santos de Freitas-Xavier; Álvaro Ferreira Júnior (Brazilian Journal of Microbiology, 2025)

Combining fermentation and vermicomposting for sustainable pet food waste management: Effects of waste profile and inoculum source - Romain Tuffou; Laurent Windal; Sébastien Delmotte; Gilbert Skorski; Isabelle Metton; Sebastien N. Voisin; Anais Surribas; Sercan Beytur; Marion Leborgne; Hélène Blanquart; Xavier Salducci; Alexandre Feugier (Waste Management, 2025)

N-Propargylpyrrolidine-based butyrylcholinesterase and monoamine oxidase inhibitors - Urban Košak; Damijan Knez; Anja Pišlar; Selena Horvat; Simon Žakelj; Alexandre Igert; José Dias; Florian Nachon; Xavier Brazzolotto; Stanislav Gobec (Chemico-Biological Interactions, 2025)

Chiral switch of a butyrylcholinesterase inhibitor for the treatment of Alzheimer's disease - Urban Košak; Damijan Knez; Svit Ferjančič Benetik; Peter Mastnak Sokolov; Anja Pišlar; Selena Horvat; Jure Stojan; Bingbing Lv; Weiting Zhang; Yuanyuan Wang; Qinjie Wang; Alexandre Igert; et al. (Chemico-Biological Interactions, 2025)

Contamination status and evaluation of metal pollution indexes in sediments from shrimp farming in the Lower São Francisco River region, Northeast Brazil - Larissa Santos Xavier; Joel Marques da Silva; Andrielle dos Santos de Jesus; João Batista Pereira; Amanda Silva de Jesus; Marcos Vinicius Teles Gomes; Sarah Adriana Rocha Soares; Andrea Novelli; Elisângela Andrade Passos; Rennan Geovanny Oliveira Araujo; Carlos Alexandre Borges Garcia; Felipo Obed Correia; et al. (Journal of Soils and Sediments, 2025)

Biomonitoring of elements airborne pollution in European Mediterranean region by two Tillandsia species - Alexandre Gonzalez; Zohra Benfodda; David Bénimélis; Damien Bourgeois; Jean-Xavier Fontaine; Roland Molinié; Patrick Meffre (Atmospheric Pollution Research, 2025)

Trace metal chemical fractionation in airborne particulate matter from a tropical urban area in Brazil - Silvânio Silvério Lopes Costa; Jeferson Cavalcante Alves; Erivaldo Vieira da Silva; Joel Marques da Silva; Larissa Santos Xavier; Vaniele Souza Ribeiro; Dayara Virgínia Lino Ávila; Sidnei Oliveira Souza; Carlos Alexandre Borges Garcia; Gisele Olímpio da Rocha; Rennan Geovanny Oliveira Araujo (Environmental Science and Pollution Research, 2025)

Stridulation sounds of the pacamã Lophiosilurus alexandri S teindachner, 1876 ( P seudopimelodidae), a threatened endemic B razilian catfish - Xavier Raick; Gregório Kurchevski; Alexandre Lima Godinho (Journal of Fish Biology, 2025)
Pseudopimelodidae comprises 49 species of freshwater catfish endemic to South America, with limited research on their acoustic behaviour. This study focuses on the pacamã Lophiosilurus alexandri Steindachner, 1876, a vulnerable catfish species endemic to the São Francisco River basin, known for its ecological and economic importance. Sound production by this species was analysed for the first time. Three individuals were recorded while being held underwater revealing the production of two distinct sound types ( type I and type II ) associated with pectoral fin movements (abduction and adduction). Sounds were 85–135 ms long with a variable number of pulses or peaks. Type II sounds were longer and louder than type I sounds , with both types showing a similar peak frequency ranging between 200 and 500 Hz. The sounds were produced alternately by the pectoral fins, with occasional lateralization. More research is needed to determine whether these sounds can be used for monitoring or if they lack sufficient species‐specific characteristics.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Legume trees in an established tropical grass pasture increase deep-soil N stocks - Diana Valadares Pessoa; Marcio Vieira da Cunha; Alexandre Carneiro Leão de Mello; Mércia Virginia Ferreira dos Santos; Giselle Gomes Monteiro Fracetto; Valéria Xavier de Oliveira Apolinário; Chrislanne Barreira de Macêdo Carvalho; Pedro Mouzinho de Oliveira Neto; José Lypson Pinto Simões Izidro; Suellen Brandão de Miranda Costa; José Carlos Batista Dubeux Junior; Janerson José Coelho (European Journal of Agronomy, 2025)

Lippia origanoides essential oil increases longevity and ameliorates β-amyloid peptide-induced toxicity in Caenorhabditis elegans - Ana Maria Henrique Moniz; Francisco Humberto Xavier Junior; Giovanna Melo Martins Silva; Ana Cristina Gonçalves Reis de Melo; Maylla Maria Correia Leite Silva; Weslley Souza Paiva; Hugo Alexandre Oliveira Rocha; Luiz Antônio Mendonça Alves da Costa; Antônio Alves de Melo Filho; Riva de Paula Oliveira (Natural Product Research, 2025)

Evaluation of metals in surface sediments from shrimp farming areas in the estuarine region of the Baixo São Francisco, in Northeastern Brazil - Larissa Santos Xavier; Raynne Aparecida de Sousa Pires; Marcos Vinicius Teles Gomes; Elisângela Andrade Passos; Joel Marques da Silva; Igor Santos Silva; Carlos Alexandre Borges Garcia; Felipo Obed Correia; Silvânio Silvério Lopes da Costa (Regional Studies in Marine Science, 2025)

Unveiling antibiofilm potential: proteins from Priestia sp. targeting Staphylococcus aureus biofilm formation - Nicole Sartori Ribeiro; Deisiane Fernanda da Rosa; Marina Amaral Xavier; Sharon Vieira dos Reis; Walter O. Beys-da-Silva; Lucélia Santi; Cristiano Valim Bizarro; Pedro Ferrari Dalberto; Luiz Augusto Basso; Alexandre José Macedo (Antonie van Leeuwenhoek, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Flooding and fire frequency promotes beta diversity in tree and non-tree species in tropical wetlands - Bruno Henrique dos Santos Ferreira; Maxwell da Rosa Oliveira; Bruno Arguelho Arrua; Vivian Ayumi Fujizawa Nacagava; Rafaela Aparecida Mariano Fernandes; Alexandre de Matos Martins Pereira; Andréia de Carvalho Santos; Ademilson Costa; Mesaque Rocha; Silvio Xavier; Rubens Aquino Ferraz; Arnildo Pott; et al. (Forest Ecology and Management, 2024)

Observation and modelling of infragravity waves at a large meso-tidal inlet and lagoon - Alexandre Nicolae Lerma; Nico Valentini; Paul Bayle; Xavier Bertin; Florian Ganthy; Arnaud Le Pevedic; Guillaume Detandt; Nadia Sénéchal (Coastal Engineering, 2024)

Comparison of the predatory impacts of indigenous and adventive ladybeetle species (Coleoptera: Coccinellidae) using a functional response approach - Fateme Ranjbar; M. Amin Jalali; Zahra Ahmadi; Xavier Pons; Alexandre Levi-Mourao; Todd Ugine (Journal of Plant Diseases and Protection, 2024)

Corrigendum: The Brazilian Santos basin underwater soundscape monitoring project (PMPAS-BS) - José Antonio Moreira Lima; William Soares Filho; Fabio C. Xavier; Thiago Pires de Paula; Angela Spengler; Fernando Gonçalves de Almeida; Diogo Peregrino Correa Pereira; Valéria Souza Rego; Cátia Galotta; Carlos Corrêa Junior; Alexandre Bazyl (Frontiers in Marine Science, 2024)

The Brazilian Santos basin underwater soundscape monitoring project (PMPAS-BS) - José Antonio Moreira Lima; William Soares Filho; Fabio C. Xavier; Thiago Pires de Paula; Angela Spengler; Fernando Gonçalves de Almeida; Diogo Peregrino Correa Pereira; Valéria Souza Rego; Cátia Galotta; Carlos Corrêa Junior; Alexandre Bazyl (Frontiers in Marine Science, 2024)
This paper describes the Santos Basin Underwater Soundscape Monitoring Project (PMPAS-BS), a Brazilian ocean soundscape monitoring initiative. The main objective of the project is to quantify and assess hydroacoustic noise of anthropogenic origin in a large sedimentary basin extending from 23° S to 28° S on the southeastern Brazilian continental margin of the South Atlantic Ocean. Noise associated with oil and gas (O&G) exploration and production activities is the primary target, but this oceanic region also has busy shipping lanes for commercial, military, and fishing vessels. The two main hubs of Brazil’s export and import of goods by sea are located in this region: Santos and Rio de Janeiro ports. The project has three measurement components: mobile monitoring based on gliders and drifting acoustic profilers, fixed shallow-water monitoring based on acoustic measurements at coastal stations near shipping lanes associated with exploration and production activities in the Santos Basin, and fixed oceanic monitoring based on deep-water mooring lines equipped with passive autonomous acoustic recorders near production units, shipping lanes, and areas with lower intensity of O&G activities (pristine or reference sites). Numerical modeling of anthropogenic underwater acoustic noise has also been included as a fourth project component. The PMPAS-BS covers an area of more than 251,000 km 2 and uses several instruments with different methods and sensors for acoustic measurements. Its results provide current sound levels over a very large region of the western South Atlantic, both in areas more and less affected by anthropogenic activities.

Phenolic-rich extract from Bryophyllum pinnatum leaf cultivated under drought stress conditions modulates the antioxidant and anti-inflammatory response - Natasha Lorenna Ferreira da Silva; Renato Dantas-Medeiros; Emanuella de Aragão Tavares; Dayanne Lopes Porto; Valéria Costa da Silva; Jacinthia Beatriz Xavier-Santos; Júlia Gabriela Ramos Passos; Weslley de Souza Paiva; Hugo Alexandre de Oliveira Rocha; Matheus de Freitas Fernandes-Pedrosa; Júlia Morais Fernandes; Silvana Maria Zucolotto (Phytochemistry Letters, 2024)

Litter Deposition and Decomposition in a Tropical Grass-Legume Silvopastoral System - Diana Valadares Pessoa; Marcio Vieira da Cunha; Alexandre Carneiro Leão de Mello; Mércia Virginia Ferreira dos Santos; Géssica Solanna Calado Soares; Dayanne Camelo; Valéria Xavier de Oliveira Apolinário; José Carlos Batista Dubeux Junior; Janerson José Coelho (Journal of Soil Science and Plant Nutrition, 2024)

Cytogenotoxicity and inflammatory response in liver of rats exposed to different doses of cannabis nano emulsions - Thiago Guedes Pinto; Barbara dos Anjos Rosario; Andrea Cristina de Moraes Malinverni; Rosana Xavier; Yasmin Alaby Martins Ferreira; Luciana Pellegrini Pisani; Pedro Everson Alexandre de Aquino; Glauce Socorro de Barros Viana; Daniel Vitor de Souza; Milena de Barros Viana; Daniel Araki Ribeiro (Archives of Toxicology, 2024)

Prevalence of cagA, cagM, vacA and oipA genes in isolates of Helicobacter pylori obtained from hospital patients in Northeast Brazil - Thaynara Millena de Oliveira Bezerra; Keyla Vitória Marques Xavier; Ana Carolina de Oliveira Luz; Isabella Macário Ferro Cavalcanti; Carlos Alexandre Antunes de Brito; Tereza Cristina Leal- Balbino (Brazilian Journal of Microbiology, 2024)

Determination of the maximum bioaccumulation capacity of various metals in leaves of two Tillandsia species - Alexandre Gonzalez; Zohra Benfodda; David Bénimélis; Damien Bourgeois; Damien Herfurth; Jean-Xavier Fontaine; Roland Molinié; Patrick Meffre (Environmental Science and Pollution Research, 2024)

El Niño Effects and Biological Parameter Comparisons of an Estuarine Resident Fish Occurring in the Sea - Erika Belarmino; Giselle Xavier Perazzo; Bianca Possamai; João Paes Vieira; Alexandre Miranda Garcia (Estuaries and Coasts, 2024)

Cryopreservation efficiency of red-rumped agouti (Dasyprocta leporina) sperm obtained from different origins through epididymal retrograde flushing or electroejaculation - Thibério de Sousa Castelo; Andréia Maria da Silva; Gislayne Christianne Xavier Peixoto; Ana Liza Paz Souza; Lívia Batista Campos; Gabriela Liberalino Lima; Maiko Roberto Tavares Dantas; João Batista Freire de Souza-Junior; Alexandre Rodrigues Silva (Cryobiology, 2023)

Nutritional and chemical composition of Alpinia zerumbet leaves, a traditional functional food - Jefferson Diocesano da Cruz; Maria A. Mpalantinos; Laena Rebouças de Oliveira; Tainara Garcia Branches; Alexandre Xavier; Francisca das Chagas do A. Souza; Jaime P. Lopes Aguiar; José Luiz P. Ferreira; Jefferson Rocha de Andrade Silva; Ana Claudia Fernandes Amaral (Food Research International, 2023)

A multiscalar and multiproxy geoarchaeological approach to site formation processes at the Middle and Upper Palaeolithic site of La Roche-à-Pierrot, Saint-Césaire, France - Dominique Todisco; Carolina Mallol; Christelle Lahaye; Guillaume Guérin; François Bachellerie; Eugène Morin; Brad Gravina; Amélie Challier; Cédric Beauval; Jean-Guillaume Bordes; Céline Colange; Laure Dayet; et al. (Quaternary Science Reviews, 2023)

Relationships among the founding ancestral genomes involved in the origin of sugarcane (Saccharum spp.) based on FISH and GISH comparative analysis - Nina Reis Soares; Gleicy K. Oliveira; Mauro Alexandre Xavier; Silvana A. Creste Dias Souza; Maria Lucia Carneiro Vieira (Brazilian Journal of Botany, 2023)

Characterization and photocatalytic performance of cement mortars with incorporation of TiO2 and mineral admixtures - Rancés Castillo Lara; Gustavo de Castro Xavier; Maria C. Canela; Juliana Alves Carvalho; Jonas Alexandre; Afonso Rangel Garcez de Azevedo (Environmental Science and Pollution Research, 2023)

Density and Dispersal Radius of Tamarixia radiata for Control of Diaphorina citri in Citrus Groves - Denis Rogério Marin; Wellington Ivo Eduardo; Alexandre José Ferreira Diniz; Marcelo Pedreira Miranda; Odimar Zanuzo Zanardi; Arthur Fernando Tomaseto; Adriano Gomes Garcia; José Roberto Postali Parra; Haroldo Xavier Linhares Volpe (Neotropical Entomology, 2023)

Persistent contamination of a hospital hot water network by Legionella pneumophila - Audrey Jeanvoine; Marion Richard; Alexandre Meunier; Sophie Chassagne; Pascal Cholley; Houssein Gbaguidi-Haore; Marlène Sauget; Xavier Bertrand; Didier Hocquet (International Journal of Hygiene and Environmental Health, 2023)

Volatile organic compound (VOC) profile and plantlet growth of Aeollanthus suaveolens under conventional and alternative membrane systems - Diene Xavier Araújo; Tainá Teixeira Rocha; Alexandre Alves de Carvalho; Ana Paula Ribeiro Medeiros; Fernanda Naiara Santos Ribeiro; Rafael Marlon Alves de Assis; Suzan Kelly Vilela Bertolucci; José Eduardo Brasil Pereira Pinto (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

New improved Brazilian daily weather gridded data (1961–2020) - Alexandre C. Xavier; Bridget R. Scanlon; Carey W. King; Aline I. Alves (International Journal of Climatology, 2022)
The demand for meteorological gridded datasets has increased within the last few years to inform studies such those in climate, weather, and agriculture. These studies require those data to be readily usable in standard formats with continuous spatial and temporal coverage. Since 2016, Brazil has a daily gridded meteorological data set with spatial resolution of 0.25° × 0.25° from January 1, 1980 to December 31, 2013 which was well received by the community. The main objective of this work is to improve the Brazilian meteorological data set. We do this by increasing the resolution of the minimum and maximum temperature (Tmax and Tmin) gridded interpolations from 0.25° × 0.25° to 0.1° × 0.1° by incorporating data on topographic relief, and increasing the time period covered (January 1, 1961–July 31, 2020). Besides Tmax and Tmin, we also gridded precipitation (pr), solar radiation (Rs), wind speed (u2), and relative humidity (RH) using observed data from 11,473 rain gauges and 1,252 weather stations. By means of ranked cross‐validation statistics, we selected the best interpolation among inverse distance weighting and angular distance weighting methods. We determined that interpolations for Tmax and Tmin are improved by using the elevation of a query point, that accounts for topographic relief, and a temperature lapse rate. Even though this new version has ≈25 years more data relative to the previous one, statistics from cross‐validation were similar. To allow researchers to assess the performance of the interpolation relative to station data in the area, we provide two types of gridded controls.

Morphoanatomy and changes in antioxidant defense associated with the natural ventilation system of micropropagated Lippia dulcis plantlets - Tainá Teixeira Rocha; Diene Xavier Araújo; André Maciel da Silva; Jean Paulo Vitor de Oliveira; Alexandre Alves de Carvalho; Manuel Losada Gavilanes; Suzan Kelly Vilela Bertolucci; Eduardo Alves; José Eduardo Brasil Pereira Pinto (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Eco-friendly ceramic bricks: a comparative study of life cycle impact methods - Josinaldo Dias; Gustavo Xavier; Afonso Azevedo; Jonas Alexandre; Henry Colorado; Carlos Maurício Vieira (Environmental Science and Pollution Research, 2022)

Initial growth and survival of Eucalyptus spp. and Mimosa caesalpiniifolia Benth. in silvopastoral systems and their impact on herbage accumulation of Urochloa decumbens Stapf R. D. Webster - Chrislanne Barreira de Macêdo Carvalho; Alexandre Carneiro Leão de Mello; Márcio Vieira da Cunha; Valéria Xavier de Oliveira Apolinário; Valdson José da Silva; Suellen Brandão de Miranda Costa; Robson Oliveira de Carvalho; Mércia Virginia Ferreira dos Santos (Agroforestry Systems, 2022)

Nutritive value of Urochloa decumbens Stapf R. D. Webster and Mimosa caesalpiniifolia Benth. and performance of cattle in monoculture and silvopastoral systems, in the Agreste region of Pernambuco - Chrislanne Barreira de Macêdo Carvalho; Alexandre Carneiro Leão de Mello; Márcio Vieira da Cunha; Valéria Xavier de Oliveira Apolinário; José Carlos Batista Dubeux Júnior; Diana Valadares Pessoa; Pedro Mouzinho de Oliveira Neto; Vanilson Pedro da Silva (Tropical Animal Health and Production, 2022)

Sustainability in Sugarcane Supply Chain in Brazil: Issues and Way Forward - Raffaella Rossetto; Nilza Patricia Ramos; Regina Celia de Matos Pires; Mauro Alexandre Xavier; Heitor Cantarella; Marcos Guimarães de Andrade Landell (Sugar Tech, 2022)

Random forest for spatialization of daily evapotranspiration (ET0) in watersheds in the Atlantic Forest - Pablo Francisco Benitez Baratto; Roberto Avelino Cecílio; David Bruno de Sousa Teixeira; Sidney Sara Zanetti; Alexandre Cândido Xavier (Environmental Monitoring and Assessment, 2022)

Molecular and morphological identification of the alfalfa weevil larval parasitoids Bathyplectes anura and Bathyplectes curculionis to estimate the rate of parasitism - Alexandre Levi-Mourao; Pilar Muñoz; Pedro Cerda-Bennasser; Roberto Meseguer; Xavier Pons (BioControl, 2022)
The alfalfa weevil ( Hypera postica Gyllenhal, Coleoptera: Curculionidae) is a major pest of alfalfa crops. Chemical control measures are inefficient, but the larvae are often infested by parasitoid wasps of the genus Bathyplectes Förster (Hymenoptera: Ichneumonidae), which offer a potential biological control strategy. The development of effective biological control requires the identification of parasitoid species, but conventional methods involve the rearing of parasitoids to the puparium stage for morphological confirmation. Here we designed a PCR method in which two pairs of primers are used to detect and identify Bathyplectes curculionis Thomson and Bathyplectes anura Thomson larvae in a faster way. We compared conventional rearing to the new method as a means to determine the parasitism rates caused by each species in Spain during the 2019 and 2020 seasons. In 2019, the PCR method detected five times as many B. curculionis events and twice as many B. anura events. Similarly, in 2020, the PCR method detected seven times as many B. curculionis events and twice as many B. anura events. High mortality of H. postica larvae was recorded in 2020 due to an epizootic attack by the fungus Zoophthora phytonomi Arthur (Zygomycetes: Entomophthorales), explaining the lower overall rate of parasitism and the widespread death of the larvae. Statistical analysis confirmed that the PCR method is more sensitive than conventional rearing for the detection of target parasitoids. However, only rearing can confirm the effective parasitism or the presence of unexpected species. We therefore recommend the use of both methods in parallel when evaluating host–parasitoid systems.

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

In vitro culture of Lippia dulcis (Trev.): light intensity and wavelength effects on growth, antioxidant defense, and volatile compound production - Taina Teixeira Rocha; Diene Xavier Araújo; Alexandre Alves de Carvalho; Carolina Mesquita Germano; Maria de Fátima Santos; Osmar Alves Lameira; Suzan Kelly Vilela Bertolucci; José Eduardo Brasil Pereira Pinto (In Vitro Cellular & Developmental Biology - Plant, 2022)

Association Mapping for Sugarcane Quality Traits at Three Harvest Times - Alisson Esdras Coutinho; Marcel Fernando da Silva; Dilermando Perecin; Roberto Carvalheiro; Mauro Alexandre Xavier; Marcos Guimarães de Andrade Landell; Luciana Rossini Pinto (Sugar Tech, 2022)

Synthesis, antibiotic modifying activity, ADMET study and molecular docking of chalcone (E)-3-(2,4-dichlorophenyl)-1-(2-hydroxyphenyl)prop-2-en-1-one in strains of Staphylococcus aureus carrying MepA efflux pumps - Janaína Esmeraldo Rocha; Thiago Sampaio de Freitas; Jayze da Cunha Xavier; Raimundo Luiz Silva Pereira; Francisco Nascimento Pereira; Carlos Emídio Sampaio Nogueira; Márcia Machado Marinho; Paulo Nogueira Bandeira; Maria Alyce Albuquerque Fernandes; Emmanuel Silva Marinho; Alexandre Magno Rodrigues Teixeira; Hélcio Silva dos Santos; et al. (Archives of Microbiology, 2022)

Subterranean “oasis” in the Brazilian semiarid region: neglected sources of biodiversity - Diego de M. Bento; Marconi Souza-Silva; Alexandre Vasconcellos; Bruno C. Bellini; Xavier Prous; Rodrigo L. Ferreira (Biodiversity and Conservation, 2021)

Prognosis of rash and chilblain-like lesions among outpatients with COVID-19: a large cohort study - Hélène Mascitti; Patrick Jourdain; Alexandre Bleibtreu; Luc Jaulmes; Agnès Dechartres; Xavier Lescure; Youri Yordanov; Aurélien Dinh; Caroline Apra; Arthur Mensch; Amélie Aime-Eusebi; Erwan Debuc; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Evaluation of trace metal accumulation in six vegetable crops intercropped with phytostabilizing plant species, in a French urban wasteland - Xavier Laffray; Kamal Toulaïb; Clarisse Balland-Bolou-Bi; Matthieu Bagard; Luis Leitao; David Huguenot; Vanessa Alphonse; Samir Abbad-Andaloussi; Alexandre Livet; Noureddine Bousserrhine; Juliette Leymarie; Anne Repellin (Environmental Science and Pollution Research, 2021)

Influence of high temperatures on physical properties and microstructure of gneiss - K. O. B. Costa; G. C. Xavier; M. T. Marvila; J. Alexandre; A. R. G. Azevedo; S. N. Monteiro (Bulletin of Engineering Geology and the Environment, 2021)

Modulations of lipid metabolism and development of the Atlantic salmon (Salmo salar) fry in response to egg-to-fry rearing conditions - Valérie Cornet; Florian Geay; Alexandre Erraud; Syaghalirwa N. M. Mandiki; Enora Flamion; Yvan Larondelle; Xavier Rollin; Patrick Kestemont (Fish Physiology and Biochemistry, 2021)

Potential of Gliricidia sepium (jacq.) Kunth ex Walp. and Mimosa caesalpiniifolia Benth. in silvopastoral systems intercropped with signalgrass [Urochloa decumbens (Stapf) R.D. Webster] - Ana María Herrera; Alexandre Carneiro Leão de Mello; Valéria Xavier de Oliveira Apolinário; José Carlos B. Dubeux Júnior; Márcio Vieira da Cunha; Mércia Virginia Ferreira dos Santos (Agroforestry Systems, 2021)

Eddy formation in the bays of Kamchatka and fluxes to the open ocean - Alexandre L’Her; Markus Reinert; Sergey Prants; Xavier Carton; Mathieu Morvan (Ocean Dynamics, 2021)

Implementing Brazil’s Forest Code: a vital contribution to securing forests and conserving biodiversity - Rebecca Catherine Brock; Andy Arnell; Will Simonson; Aline C. Soterroni; Aline Mosnier; Fernando Ramos; Alexandre Xavier Ywata de Carvalho; Gilberto Camara; Johannes Pirker; Michael Obersteiner; Valerie Kapos (Biodiversity and Conservation, 2021)
Meeting Brazil’s ambitious national commitments on both climate change mitigation and biodiversity conservation depends on securing its reserves of forest carbon and biodiversity. Brazil’s ‘Forest Code’ is a key tool to reconcile environmental preservation and agricultural production; it limits deforestation and requires forest restoration in illegally deforested areas. However, not all provisions of the law’s 2012 revision have yet been implemented and some are facing new challenges. Using modelled land use change projections for the whole of the country, we show that full implementation and enforcement of the law has the potential to contribute to conserving biodiversity. Biodiversity outcomes will be especially positive if (i) deforested areas are restored in ways that support recolonization by native species and (ii) additional measures are implemented to protect native vegetation in areas like Caatinga dry forests and Cerrado savannas, which may experience added pressure displaced from other regions by Forest Code implementation.

Acoustic homogeneity in the piranha Serrasalmus maculatus - Xavier Raick; Rodney Rountree; Gregório Kurchevski; Francis Juanes; Alessia Huby; Alexandre L. Godinho; Éric Parmentier (Journal of Fish Biology, 2021)
Different studies suggest some social calls could be used in fish identification if their specificity is unambiguously assessed. Sounds of different populations of piranhas Serrasalmus maculatus Kner, 1858 were recorded to determine their homogeneity between rivers inside a single basin (Araguari and Grande River, upper Paraná River basin) and between separated basins (Amazon and Paraná basins). All fish from the different populations produced sounds with similar acoustic features. Consequently, the populations were not discernible based on individual sound characteristics. This high homogeneity between sounds from different populations indicates their usefulness for conservation projects using passive acoustic monitoring in piranhas. Moreover, it supports the use of acoustic features as complementary key characteristics in taxonomic studies.

Cerebral Vasoreactivity as an Indirect MRI Marker of White Matter Tracts Alterations in Multiple Sclerosis - Jeremy Deverdun; Arthur Coget; Xavier Ayrignac; Clarisse Carra-Dalliere; Alexandre Krainik; Aude Metzger; Pierre Labauge; Nicolas Menjot de Champfleur; Emmanuelle Le Bars (Brain Topography, 2021)

Structure and Dynamics of the Ras al Hadd Oceanic Dipole in the Arabian Sea - Adam Ayouche; Charly De Marez; Mathieu Morvan; Pierre L’Hegaret; Xavier Carton; Briac Le Vu; Alexandre Stegner (Oceans, 2021)
The Ras al Hadd oceanic dipole is a recurrent association of a cyclone (to the northeast) and of an anticyclone (to the southwest), which forms in summer and breaks up at the end of autumn. It lies near the Ras al Hadd cape, southeast of the Arabian peninsula. Its size is on the order of 100 km. Along the axis of this dipole flows an intense jet, the Ras al Had jet. Using altimetric data and an eddy detection and tracking algorithm (AMEDA: Angular Momentum Eddy Detection and tracking Algorithm), we describe the life cycle of this oceanic dipole over a year (2014–2015). We also use the results of a numerical model (HYCOM, the HYbrid Coordinate Ocean Model) simulation, and hydrological data from ARGO profilers, to characterize the vertical structure of the two eddies composing the dipole, and their variability over a 15 year period. We show that (1) before the dipole is formed, the two eddies that will compose it, come from different locations to join near Ras al Hadd, (2) the dipole remains near Ras al Hadd during summer and fall while the wind stress (due to the summer monsoon wind) intensifies the cyclone, (3) both the anticyclone and the cyclone reach the depth of the Persian Gulf Water outflow, and (4) their horizontal radial velocity profile is often close to Gaussian but it can vary as the dipole interacts with neighboring eddies. As a conclusion, further work with a process model is recommended to quantify the interaction of this dipole with surrounding eddies and with the atmosphere.

Decomposition of senescent leaves of signalgrass (Urochloa decumbens Stapf. R. Webster) and arboreal legumes in silvopastoral systems - Ana María Herrera; Alexandre Carneiro Leão de Mello; Valéria Xavier de Oliveira Apolinário; José Carlos Batista Dubeux Júnior; Valdson José da Silva; Mércia Virginia Ferreira dos Santos; Márcio Vieira da Cunha (Agroforestry Systems, 2020)

Yellow‐eyed piranhas produce louder sounds than red‐eyed piranhas in an invasive population of Serrasalmus marginatus - Xavier Raick; Alessia Huby; Gregório Kurchevski; Alexandre L. Godinho; Éric Parmentier (Journal of Fish Biology, 2020)
Serrasalmus marginatus is a piranha species native from the lower Paraná River basin and has been invasive in the upper Paraná River basin since the 1980s. In piranhas, sounds of different species have different features. The aim of this study was to investigate if the sounds produced by this species could be used to distinguish two morphotypes: red‐ and yellow‐eyed S. marginatus from the Araguari River (upper Paraná River basin). All the temporal and frequency features of the sounds were equivalent in both groups of eye colour; it corresponds to the species‐specific signature described for S. marginatus . Nonetheless, the amplitude features were all statistically different between red‐ and yellow‐eyed piranhas. Yellow‐eyed specimens produced louder sounds. In different fish species, colour change in eyes can be due to the absence or the presence of a dominant allele. It can also be involved in social rank or during reproduction. Different hormones and neuropeptides can modulate vocal features. It is hypothesized that a mutation or different hormonal concentrations could explain both sound amplitude and eye colour playing a role in animal communication in S. marginatus .

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

An update of the Worldwide Integrated Assessment (WIA) on systemic pesticides. Part 4: Alternatives in major cropping systems - Andrea Veres; Kris A. G. Wyckhuys; Jozsef Kiss; Ferenc Tóth; Giovanni Burgio; Xavier Pons; Carlos Avilla; Stefan Vidal; Jaka Razinger; Renata Bazok; Ewa Matyjaszczyk; Ivan Milosavljević; et al. (Environmental Science and Pollution Research, 2020)
We present a synthetic review and expert consultation that assesses the actual risks posed by arthropod pests in four major crops, identifies targets for integrated pest management (IPM) in terms of cultivated land needing pest control and gauges the implementation “readiness” of non-chemical alternatives. Our assessment focuses on the world’s primary target pests for neonicotinoid-based management: western corn rootworm (WCR, Diabrotica virgifera virgifera ) in maize; wireworms ( Agriotes spp.) in maize and winter wheat; bird cherry-oat aphid ( Rhopalosiphum padi ) in winter wheat; brown planthopper (BPH, Nilaparvata lugens ) in rice; cotton aphid ( Aphis gossypii ) and silver-leaf whitefly (SLW, Bemisia tabaci ) in cotton. First, we queried scientific literature databases and consulted experts from different countries in Europe, North America, and Asia about available IPM tools for each crop-pest system. Next, using an online survey, we quantitatively assessed the economic relevance of target pests by compiling country-level records of crop damage, yield impacts, extent of insecticide usage, and “readiness” status of various pest management alternatives (i.e., research, plot-scale validation, grower-uptake). Biological control received considerable scientific attention, while agronomic strategies (e.g., crop rotation), insurance schemes, decision support systems (DSS), and innovative pesticide application modes were listed as key alternatives. Our study identifies opportunities to advance applied research, IPM technology validation, and grower education to halt or drastically reduce our over-reliance on systemic insecticides globally.

Lawsone, a 2-hydroxy-1,4-naphthoquinone from Lawsonia inermis (henna), produces mitochondrial dysfunctions and triggers mitophagy in Saccharomyces cerevisiae - Mariana Rodrigues Xavier; Manuella Maria Silva Santos; Maise Gomes Queiroz; Mariza S. de Lima Silva; Alexandre José S. Goes; Marcos Antonio De Morais Jr (Molecular Biology Reports, 2020)

Proximate causes and fitness consequences of double brooding in female barn owls - Jabi Zabala; Xavier Lambin; Julien Soufflot; Philibert Soufflot; Delphine Chenesseau; Alexandre Millon (Oecologia, 2020)

Cytochrome P450 2A6 and 2B6 polymorphisms and smoking cessation success in patients treated with varenicline - Paulo Roberto Xavier Tomaz; Mariana Soares Kajita; Juliana Rocha Santos; Jaqueline Scholz; Tânia Ogawa Abe; Patrícia Viviane Gaya; José Eduardo Krieger; Alexandre Costa Pereira; Paulo Caleb Júnior Lima Santos (European Journal of Clinical Pharmacology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

The Residual Center of Mass: An Image Descriptor for the Diagnosis of Alzheimer Disease - Alexandre Yukio Yamashita; Alexandre Xavier Falcão; Neucimar Jerônimo Leite (Neuroinformatics, 2019)

Pulp and Paper Mill Effluent Treated by Combining Coagulation-Flocculation-Sedimentation and Fenton Processes - Mariana Grötzner; Emeline Melchiors; Luiz Henrique Schroeder; Alexandre Renato dos Santos; Kethlyn Ghellere Moscon; Marco Antonio de Andrade; Sérgio Henrique Saavedra Martinelli; Claudia Regina Xavier (Water, Air, & Soil Pollution, 2018)

Jaguar movement database: a GPS‐based movement dataset of an apex predator in the Neotropics - Ronaldo G. Morato; Jeffrey J. Thompson; Agustin Paviolo; Jesus A. de La Torre; Fernando Lima; Roy T. McBride; Rogerio C. Paula; Laury Cullen; Leandro Silveira; Daniel L. Z. Kantek; Emiliano E. Ramalho; Louise Maranhão; et al. (Ecology, 2018)
The field of movement ecology has rapidly grown during the last decade, with important advancements in tracking devices and analytical tools that have provided unprecedented insights into where, when, and why species move across a landscape. Although there has been an increasing emphasis on making animal movement data publicly available, there has also been a conspicuous dearth in the availability of such data on large carnivores. Globally, large predators are of conservation concern. However, due to their secretive behavior and low densities, obtaining movement data on apex predators is expensive and logistically challenging. Consequently, the relatively small sample sizes typical of large carnivore movement studies may limit insights into the ecology and behavior of these elusive predators. The aim of this initiative is to make available to the conservation‐scientific community a dataset of 134,690 locations of jaguars ( Panthera onca ) collected from 117 individuals (54 males and 63 females) tracked by GPS technology. Individual jaguars were monitored in five different range countries representing a large portion of the species’ distribution. This dataset may be used to answer a variety of ecological questions including but not limited to: improved models of connectivity from local to continental scales; the use of natural or human‐modified landscapes by jaguars; movement behavior of jaguars in regions not represented in this dataset; intraspecific interactions; and predator‐prey interactions. In making our dataset publicly available, we hope to motivate other research groups to do the same in the near future. Specifically, we aim to help inform a better understanding of jaguar movement ecology with applications towards effective decision making and maximizing long‐term conservation efforts for this ecologically important species. There are no costs, copyright, or proprietary restrictions associated with this data set. When using this data set, please cite this article to recognize the effort involved in gathering and collating the data and the willingness of the authors to make it publicly available.

Light quality in plant tissue culture: does it matter? - Diego Silva Batista; Sergio Heitor Sousa Felipe; Tatiane Dulcineia Silva; Kamila Motta de Castro; Talita Cristina Mamedes-Rodrigues; Natane Amaral Miranda; Anyela Marcela Ríos-Ríos; Daniele Vidal Faria; Evandro Alexandre Fortini; Kristhiano Chagas; Gabriela Torres-Silva; Aloisio Xavier; et al. (In Vitro Cellular & Developmental Biology - Plant, 2018)

Toxicity of TiO2 nanoparticles on the NRK52E renal cell line - Xavier Valentini; Lara Absil; Guy Laurent; Alexandre Robbe; Sophie Laurent; Robert Muller; Alexandre Legrand; Denis Nonclercq (Molecular & Cellular Toxicology, 2017)

New Insights on Temporal Lobe Epilepsy Based on Plasticity-Related Network Changes and High-Order Statistics - Erika Reime Kinjo; Pedro Xavier Royero Rodríguez; Bianca Araújo dos Santos; Guilherme Shigueto Vilar Higa; Mariana Sacrini Ayres Ferraz; Christian Schmeltzer; Sten Rüdiger; Alexandre Hiroaki Kihara (Molecular Neurobiology, 2017)

Arcobacter spp. in fecal samples from Brazilian farmed caimans (Caiman yacare, Daudin 1802) - Maria Gabriela Xavier Oliveira; Leandro Nogueira Pressinotti; Giovane Spínola Carvalho; Mirela Caroline Vilela Oliveira; Luisa Zanolli Moreno; Carlos Emilio Cabrera Matajira; Alessandro Spínola Bergamo; Victor Manuel Aleixo; Alexandre Caixeta Veiga; Elvis de Souza Corsino; Ana Paula Guarnieri Christ; Maria Inês Zanolli Sato; et al. (Tropical Animal Health and Production, 2017)

Daily gridded meteorological variables in Brazil (1980–2013) - Alexandre C. Xavier; Carey W. King; Bridget R. Scanlon (International Journal of Climatology, 2016)
Basic meteorological data are essential for evaluating impacts of spatiotemporal variability in climate forcing on hydrology and agroecosystems. The objective of this work was to develop high‐resolution grids (0.25 ∘ × 0.25 ∘ ) of daily precipitation, evapotranspiration, and the five climate variables generally required to estimate evapostranspiration for Brazil. These five variables are maximum and minimum temperature, solar radiation, relative humidity, and wind speed. We tested six different interpolation schemes to create the grids for these variables. The data were obtained from 3625 rain gauge and 735 weather stations for period of 1980–2013. We used a cross‐validation approach that compares point observed data to point interpolated estimates to select the best interpolation scheme for each climate variable. We also present the performance of the best interpolation for each climate variable at daily timescales and for river basins. The inverse distance weighting and angular distance weighting methods produced the best results. Performance of all methods was poorer prior to 1995 because of fewer stations and available data. The performance of the interpolation varies for different seasons for almost all variables. Forecasting capability was tested for precipitation only and performed adequately for the system state (wet or dry). Variations in the interpolation schemes across river basins are primarily attributed to differences in gauge or station network density. This freely available gridded meteorological data set significantly advances the availability of climate data in Brazil.

Vitamin D receptor polymorphisms and expression profile in rheumatoid arthritis brazilian patients - Catarina Addobbati Jordão Cavalcanti; Jaqueline de Azevêdo Silva; Will de Barros Pita; Tiago Degani Veit; Odirlei Andre Monticielo; Ricardo Machado Xavier; João Carlos Tavares Brenol; Cleiton Viegas Brenol; Thiago Sotero Fragoso; Alexandre Domingues Barbosa; Ângela Luiza Branco Pinto Duarte; Renê Donizeti Ribeiro Oliveira; et al. (Molecular Biology Reports, 2016)

CYP2B6 rs2279343 polymorphism is associated with smoking cessation success in bupropion therapy - Paulo Roberto Xavier Tomaz; Juliana Rocha Santos; Jaqueline Scholz Issa; Tânia Ogawa Abe; Patrícia Viviane Gaya; José Eduardo Krieger; Alexandre Costa Pereira; Paulo Caleb Júnior Lima Santos (European Journal of Clinical Pharmacology, 2015)

Is low-input management system a good selection environment to screen winter wheat genotypes adapted to organic farming? - Antonin Le Campion; François-Xavier Oury; Jean-Yves Morlais; Patrice Walczak; Paul Bataillon; Olivier Gardet; Stéphane Gilles; Alexandre Pichard; Bernard Rolland (Euphytica, 2014)

Dampening prey cycle overrides the impact of climate change on predator population dynamics: a long‐term demographic study on tawny owls - Alexandre Millon; Steve J. Petty; Brian Little; Olivier Gimenez; Thomas Cornulier; Xavier Lambin (Global Change Biology, 2014)

BAC-end sequences analysis provides first insights into coffee (Coffea canephora P.) genome composition and evolution - Alexis Dereeper; Romain Guyot; Christine Tranchant-Dubreuil; François Anthony; Xavier Argout; Fabien de Bellis; Marie-Christine Combes; Frederick Gavory; Alexandre de Kochko; Dave Kudrna; Thierry Leroy; Julie Poulain; et al. (Plant Molecular Biology, 2013)

Current and future atmospheric circulation at 500 hPa over Greenland simulated by the CMIP3 and CMIP5 global models - Alexandre Belleflamme; Xavier Fettweis; Charlotte Lang; Michel Erpicum (Climate Dynamics, 2013)

Biological control of pathogen communication in the rhizosphere: A novel approach applied to potato soft rot due to Pectobacterium atrosepticum - Alexandre Crépin; Corinne Barbey; Amélie Cirou; Mélanie Tannières; Nicole Orange; Marc Feuilloley; Yves Dessaux; Jean-François Burini; Denis Faure; Xavier Latour (Plant and Soil, 2012)

First fossil evidence of an “interglacial refugium” in the Pyrenean region - Juan Manuel López-García; Hugues-Alexandre Blain; Ethel Allué; Sandra Bañuls; Amelia Bargalló; Patricia Martín; Juan Ignacio Morales; Mireia Pedro; Anna Rodríguez; Alex Solé; F. Xavier Oms (The Science of Nature, 2010)

Defense Proteins from Vigna Unguiculata Seed Exudates: Characterization and Inhibitory Activity Against Fusarium Oxysporum - Tatiana L. Rose; Alexandre da Silva Conceição; Jose Xavier-Filho; Lev A. Okorokov; Kátia V. S. Fernandes; Francis Marty; Danièle Marty-Mazars; André O. Carvalho; Valdirene M. Gomes (Plant and Soil, 2006)